Synthesis and Target Identification of Benzoxepane Derivatives as Potential Anti‐Neuroinflammatory Agents for Ischemic Stroke. Issue 6 (27th December 2019) - Gao, Cheng‐Long; Hou, Gui‐Ge; Liu, Jin; Ru, Tong; Xu, Ya‐Zhou; Zhao, Shun‐Yi; Ye, Hui; Zhang, Lu‐Yong; Chen, Kai‐Xian; Guo, Yue‐Wei; Pang, Tao; Li, Xu‐Wen
Abstract: Benzoxepane derivatives were designed and synthesized, and one hit compound emerged as being effective in vitro with low toxicity. In vivo, this hit compound ameliorated both sickness behavior through anti‐inflammation in LPS‐induced neuroinflammatory mice model and cerebral ischemic injury through anti‐neuroinflammation in rats subjected to transient middle cerebral artery occlusion. Target fishing for the hit compound using photoaffinity probes led to identification of PKM2 as the target protein responsible for anti‐inflammatory effect of the hit compound. Furthermore, the hit exhibited an anti‐neuroinflammatory effect in vitro and in vivo by inhibiting PKM2‐mediated glycolysis and NLRP3 activation, indicating PKM2 as a novel target for neuroinflammation and its related brain disorders. This hit compound has a better safety profile compared to shikonin, a reported PKM2 inhibitor, identifying it as a lead compound in targeting PKM2 for the treatment of inflammation‐related diseases. Abstract : Fishing around : The benzoxepane derivative A was effective in vivo, ameliorating both sickness behavior through anti‐inflammation in LPS‐induced neuroinflammatory mice model and cerebral ischemic injury through anti‐neuroinflammation in rats subjected to transient middle cerebral artery occlusion. Target fishing identified PKM2 as the target protein for A . Furthermore, A exhibited an anti‐neuroinflammatory effect in vitro and in vivo by inhibiting PKM2‐mediated glycolysis and NLRP3 activation.